BRAF mutation is not associated with an increased risk of recurrence in patients undergoing resection of colorectal liver metastases. Issue 9 (10th June 2019) - Bachet, J-B; Moreno-Lopez, N; Vigano, L; Marchese, U; Gelli, M; Raoux, L; Truant, S; Laurent, C; Herrero, A; Le Roy, B; Deguelte Lardiere, S; Passot, G; et al.
Abstract: Background: BRAF mutation is associated with a poor prognosis in patients with metastatic colorectal cancer. For patients with resectable colorectal liver metastases (CRLMs), the prognostic impact of BRAF mutation is unknown and the benefit of surgery debated. This nationwide intergroup (ACHBT, FRENCH, AGEO) study aimed to evaluate the oncological outcome of patients undergoing liver resection for BRAF -mutated CRLMs. Methods: The study included patients who underwent resection for BRAF -mutated CRLMs in 24 centres between 2012 and 2016. A case-matched comparison was made with 183 patients who underwent resection of CRLMs with wild-type BRAF during the same interval. Results: Sixty-six patients who underwent resection for BRAF -mutated CRLMs in 24 centres were compared with 183 patients with wild-type BRAF . The 1- and 3-year disease-free survival (DFS) rates were 46 and 19 per cent for the BRAF -mutated group, and 55·4 and 27·8 per cent for the group with wild-type BRAF ( P = 0·430). In multivariable analysis, BRAF mutation was not associated with worse DFS (hazard ratio 1·16, 95 per cent c.i. 0·72 to 1·85; P = 0·547). The 1- and 3-year overall survival rates after surgery were 94 and 54 per cent respectively among patients with BRAF mutation, and 95·8 and 82·9 per cent in those with wild-type BRAF ( P = 0·004). Median survival after disease progression was 23·0 (95 per cent c.i. 11·0 to 35·0) months among patients with mutated BRAF and 44·3 (35·9 to 52·6) months in those with wild-type BRAF ( P = 0·050). Multisite disease progression was more common in the BRAF -mutated group (48 versus 29·8 per cent; P = 0·034). Conclusion: These results support surgical treatment for resectable BRAF- mutated CRLM, as BRAF mutation by itself does not increase the risk of relapse after resection. BRAF mutation is associated with worse survival in patients whose disease relapses after resection of CRLM, as for non-metastatic colorectal cancer. Graphical Abstract: For patients with resectable colorectal liver metastases, the prognostic impact of BRAF mutation is unknown and the benefit of surgery debated. This nationwide case–control study showed that BRAF mutation by itself does not increase the risk of relapse after surgery, but is associated with worse survival after relapse. wtBRAF, wild-type BRAF ; mut BRAF, mutated BRAF . No effect on recurrence